Small Business Taxation : Reform to Encourage Formality and Firm Growth - Loeprick, Jan (World Bank, Washington, DC, 2012)
Reforming a tax system for small businesses is complicated. No single best practice can solve all the issues that arise in trying to implement a tax system that is simple, administer-able, and equitable. This note presents a menu of considerations and 'good practice' options. It is the first in a series of five notes addressing issues that governments of developing countries face in reforming their tax systems.